AN INTRODUCTION TO VEDANTA’S INTERPRETATION BY SWAMI VIVEKANAND (International Journal of Food and Nutritional Sciences, 2022)
Vedanta is one of the best and most influential schools of Indian thought. Vedanta's philosophy seems difficult for us to understand. But Vivekananda gave a new understanding of Vedanta in a way that everyone can understand it effortlessly. He wanted to free Vedanta from metaphysical and theological dogmas so that everyone could tolerate it. The word Vedanta is a Sanskrit word consisting of two simple words: Veda and Anta. The Sanskrit word "Veda" is derived from the word "vid" meaning "to know or have knowledge " and " anta " meaning " end " or " goal". Vedanta The best explanation of Vedic concepts is found in Vedanta. This is a wonderful reflection and interpretation of Indian thought representing unity behind differences. Vedanta talks about many problems of the human mind, such as why we are born, where we come from, the reason for our creation, what is the purpose of this world, what is the connection of our mind and inner self with the body. What. Charting the historical development of Vedic philosophy, Vedanta captures the teachings of different Vedic schools, their support and differences. This article attempts to focus on Swami Vivekananda's views on Vedanta philosophy. Swami Vivekananda summarized all of Vedanta and its practices in his famous aphorism: "Every soul has the potential for divinity". The goal is to embody inner divinity by controlling the inner and outer. Do this by studying, praying, mind-controlling, or meditating. The main approach of Vedanta is to seek truth and at the same time try to provide a basis for morality. Satyam (truth), Shivam (good) and Sundaram (beauty) are practical concepts.